Aggregatibacter actinomycetemcomitans serotype prevalence and antibiotic resistance in a UK population with periodontitis. (September 2017) - Akrivopoulou, Chaido; Green, Ingrid M.; Donos, Nikolaos; Nair, Sean P.; Ready, Derren
Highlights: Serotype a was most common Aggregatibacter actinomycetemcomitans serotype in a UK cohort. All A. actinomycetemcomitans isolates were resistant to penicillin and metronidazole. 83.9% of isolates were resistant to amoxicillin. Abstract: Objectives: Aggregatibacter actinomycetemcomitans is a recognised pathogen involved in aggressive periodontitis. Seven serotypes of A. actinomycetemcomitans exist with a range of virulence and distribution dependent on ethnicity and geography. The ability of A. actinomycetemcomitans to invade soft tissue can necessitate the use of systemic antibiotics for treatment, however variations in its antibiotic susceptibility exist dependent on geographical location. Methods: Serotypes of A. actinomycetemcomitans isolates from a UK cohort of 50 patients with aggressive periodontitis were determined by PCR. Resistance of the isolates to eight antibiotics [penicillin (1 U), amoxicillin (2 μg), amoxicillin/clavulanic acid (30 μg), metronidazole (5 μg), clindamycin (2 μg), tetracycline (10 μg), ciprofloxacin (5 μg) and ceftazidime (30 μg)] were determined by disk diffusion according to BSAC guidelines. Results: Prevalences of serotypes a, c, b, e and mixed serotypes were 48%, 22%, 2%, 2% and 12%, respectively. The serotype of isolates from seven patients (14%) could not be deduced by PCR. Of the 56 isolates tested, 100% were resistant to penicillin and metronidazole, 87.5% to clindamycin, 83.9% to amoxicillin and 76.8% to ceftazidime. Low rates of resistance to tetracycline (8.9% resistant) and amoxicillin/clavulanic acid (14.3% resistant) were observed, whereas no isolates were resistant to ciprofloxacin. Conclusions: As in a number of publications the suggested treatment of aggressive periodontitis includes the combined use of amoxicillin with metronidazole, these results highlight the need for culture and antimicrobial susceptibility investigations in patients with aggressive periodontitis prior to systemic use of antibiotics concomitantly to periodontal therapy.